Japan’s responses to China’s rise : soft balancing in Southeast Asia - Singh, Bhubhindar (2022)
Japan’s threat perceptions toward China have hardened over the post-Cold War period. This led Tokyo to rely more on overt balancing strategies compared with engagement and hedging strategies. While hard balancing measures are widely discussed in the literature, little or no attention is paid to soft balancing. Though concerned about China’s strategic rise, Japan’s strategic options are limited by the entrenched normative constraints within the security policymaking structure. These conditions make soft balancing a critical and viable strategy for Japan. The prominence of soft balancing is illustrated by analyzing Japan’s response to China’s widening influence in Southeast Asia, primarily focusing on two areas–East Asian multilateralism and the South China Sea territorial disputes. Empirically, this paper offers a more nuanced analysis of Japan’s response to China’s strategic rise; and theoretically, explains the way Japan’s case strengthens the conceptual utility of soft balancing through the incorporation of a normative perspective.